ANALISIS PERAN KREDIT PRODUKTIF PADA BANK PERKREDITAN RAKYAT CENTRADANA KAPUAS TERHADAP TINGKAT PENDAPATAN USAHA NASABAH DI KOTA PONTIANAK - Rustandi, Dody (Jurnal Pembangunan dan Pemerataan, 2013)
The problem of this study is "What is the role of productive loans given by banks centradana kapauas against business income respondents and the factors that influence the demand for bank credit decision centradana Kapuas Pontianak city. The purpose of this study is to investigate and analyze the role of productive credit and factors - factors that affect the demand for bank credit decision centradana Kapuas against business income customers in the city of Pontianak. The research method used is descriptive method is a method of analysis that describes an actual state of facts in order to obtain the data to be processed and then processed further in order to obtain a conclusion. With quantitative analysis tool that analyzes by performing calculations on the data obtained from questionnaires submitted to a number of respondents (bank customers), using percentage analysis by classifying the subsequent response from the customer is presented in tabular form and analyzed. Sources of data are primary data and secondary data, while the data collection techniques in doing the survey, filling questionnaires and interviews as well as data from related agencies. the number of respondents was 100 orng study consisting of 76 men and 24 women. From this research could result in the role of credit in the bank earning centradana Kapuas is going according to expectations / goals BPR bank, because all the clients to use the funds for working capital loans 100.00%. Most of the work done is the Entrepreneur (61.00%), Merchants of (34.00%), Fishing / Farming by (4.00%), Industrial and Household by (1.00%). Loans are used by bank customers centradana Kapuas Pontianak for venture capital to increase their monthly pendapataan more than Rp. 2000000-4000000 as much (41.00%), customers whose income increased from 5 million to 10 million customers or as many as 30 (30.00%), and (2.00%) of whole or 2 customers clients have incomes of less than 1 million / month. These results indicate that the role of productive loans are very helpful and was able to increase revenues for clients who need capital.